(untitled) (Bangladesh Journal of Botany, 2025)
In this study, Polygonum plebeium R. Br. underwent extensive chemical and biological investigations. Repeated chromatographic separation and spectroscopic analysis afforded caffeic acid (1) and β-sitosterol (2) from P. plebeium for the first time. Methanolic extract of P. plebeium (MEPP) and its different Kupchan fractions were evaluated for in vitro antioxidant, antibacterial and in vivo antidiarrheal, analgesic activities in mice model. The n-hexane fraction showed DPPH scavenging activity with IC50 value 24.2 µg/ml. Both n-hexane and ethyl acetate fractions exhibited activity against Pseudomonas aeruginosa with a zone of inhibition of 20.0 and 14.0 mm, respectively. Oral administration of the MEPP (200 mg/kg bw) effectively (p<0.01) reduced castor oil-induced diarrhea by 58.70% at 4h of observation period. In the acetic acid induced writhing study, MEPP at 400 mg/kg bw demonstrated a significant (p<0.001) inhibition of writhing responses by 50.0% where the standard diclofenac-Na (10 mg/kg) showed 77.91% inhibition in mice. During tail immersion method, the MEPP demonstrated a substantial (p<0.001) reduction in pain sensation in mice. The promising bioactivities observed in this study underscore the need for further investigations to isolate and identify the compounds along with their mode of action responsible for these effects. Bangladesh J. Bot. 54(1): 25-31, 2025 (March)